Language and social representations: reading, writing and press (Encuentros, 2020)
Language and social representations: reading, writing and press The research Representaciones sociales de los talleristas de Prensa Escuela sobre literacidad y prensa, which is carried out in agreement between the newspaper El Colombiano, the Pontifical Bolivarian University and the University of San Buenaventura in the ESINED research group, identified through a qualitative methodology with an interpretive approach, key issues on how young people shape in their day-to-day reading and writing, which although related to the academic field also operate in other relevant instances, it was also inquired about the place of the press in everyday life, since these three elements are the work axes of the Program to achieve one of its central objectives: the construction of citizenship. It is intended here, from the conceptions of young people to offer a reflection that broadens horizons of understanding for the strengthening of training processes in terms of reading, writing and press, and citizen competencies, which, although starting from the Prensa Escuela Program, can be expanded to the educational field.